The development of a KIM behavioural framework to support science and technology knowledge transfer in the UK defence sector. A case study approach - Darby, Roger; Kirke, Charles M. St G. (World Scientific Publishing, 2016)
A framework is presented for investigating and understanding human behaviour connected with knowledge and information management (KIM), developed from a case study in the UK defence sector. Qualitative research was undertaken in three organisations within the wider defence and security sector. The research showed that particular areas of sensitivity leading to resistance to change when KIM systems were introduced include a perceived lack of usability of KIM IT systems, the length of time required to learn how to use them, their perceived lack of reliability and the users’ consequent lack of trust in them. These issues led to the widespread use of “work arounds” to cope with the demands of the job without using the KIM systems as designed. The framework’s purpose is to contribute to the current field of knowledge about how organisations can best approach and implement required KIM changes, taking these human issues into account.
Keywords: Absorptive capacity; knowledge management; managing change; public sector management